0181 Associations between pre-defined occupational job tasks and breast cancer risk. (23rd June 2014) - Rabstein, Sylvia; Pesch, Beate; Harth, Volker; Justenhoven, Christina; Hamann, Ute; Brauch, Hiltrud; Ko, Yon; Bruening, Thomas
Abstract : Objectives: The role of occupational exposures in agricultural and industrial settings has been addressed in several breast cancer studies. Recently, the influence of shift work in nurses added as an occupational hazard that has been intensively discussed. Here, we investigate the association of job tasks in the industrial and health sector and breast cancer in a large case-control study. Method: The population-based case-control study Gene-ENvironment Interaction and Breast CAncer (GENICA) was conducted in the Greater Region of Bonn, Germany. Occupational history and job task information were collected in computer-assisted interviews. Thirty pre-defined job tasks were assessed for 1143 cases and 1155 controls in addition to the occupational history. Risk estimates were calculated as odds ratios (ORs) with 95% confidence intervals (CIs) conditional on age and adjusted for potential confounders. Results: First preliminary results indicate an increased age-adjusted risk for women who ever worked in anaesthesia (OR 1.87; 95% CI 1.03–8.0), based on fourteen cases and five controls. Conclusions: Our study revealed an increased risk for ever working in anaesthesia. This elevated risk might origin from chemical exposures or night shift work. Interactions between exposures and night work might be relevant in the progression of breast cancer. However, the results of this study are limited by the low prevalence of risk jobs and specific exposures.